Second Handed Computer Purchasing Web-Based System - Elgweal, Osama Ahmed A. (2008)
In this paper we describe a web-based information system, which serves for a first contract between a university seller and buyers of second-handed computer materials. We describe advantages of an involvement of the transaction into the virtual space within a university. Our e-transaction system covers the whole sales and buys process. The objective is to make the communication between the buyer and the seller more effective and consequently to achieve considerable time and resource savings at the both parts when it comes to purchase second-hand computer material virtually.